9m-23=53

Simple and best practice solution for 9m-23=53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m-23=53 equation:


Simplifying
9m + -23 = 53

Reorder the terms:
-23 + 9m = 53

Solving
-23 + 9m = 53

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '23' to each side of the equation.
-23 + 23 + 9m = 53 + 23

Combine like terms: -23 + 23 = 0
0 + 9m = 53 + 23
9m = 53 + 23

Combine like terms: 53 + 23 = 76
9m = 76

Divide each side by '9'.
m = 8.444444444

Simplifying
m = 8.444444444

See similar equations:

| 7(x+6)+7x=9 | | (4x+3)(3x-18)= | | 5.5j+3=-6.5j+3 | | 4x-18=x+10 | | x^3-12*x+16=0 | | 7(3p+8)=2(p+q) | | 5-2(x+3)=3-x | | logx=4.76 | | 2p-6=8+5(p+9) | | x+.07x=10000 | | x+.7x=10000 | | (4-x)(2x-5)=0 | | 4t=3t*3 | | 5K=2.5 | | 5(x+6)=4(x-7)+x | | 2(n+8)=16+2n | | 25-6x=11-8x | | 3xy-3x-y=0 | | 6x+6=-42-2x | | 8(x+2)+6=8x+7 | | -1=x^2-12 | | 5(3c-3)=4c+5 | | 6(k-7)-2=5 | | 1+12x=21+x | | a^2=744-x^2+x^2 | | 8ax+bx=0 | | 8ax+bx+28a^2x^2+8abx^2=-36 | | -3(6y-10)-y=-4(y-3) | | 10x+2x=156 | | 3(x-12)=12x | | 3a^2x^2+8abx+4b^2=-36 | | 3x+46=-4x(x+6) |

Equations solver categories